Competitive intelligence in services organizations: a systematic literature review - Cruz, Danielle Faust (2015)
It is growing the importance of services sector in the global economy. Facing a global and dynamic market, characterized by fierce competition, Competitive Intelligence - CI can help services organizations in decision making process and in the conception of competitive advantages against competitors. This paper aims to outline the state of art concerning the use of competitive intelligence in the services sector organizations, through research and analysis of articles found in major databases. This is a theoretical study consisting of a systematic literature review including bibliometric and content analysis. Relevant publications were retrieved in the following data bases related to the subject: Web of Knowledge, Scopus, Ebsco, ScienceDirect, and Engineering Village. The results allow considering the importance of competitive intelligence for survival and competitiveness of services organizations. Finally, it was verified the existence of a gap related to prescriptive studies, focusing on investigations about the subject, being this type of study relevant to the area to reach maturity